2021
DOI: 10.1039/d1qo00497b
|View full text |Cite
|
Sign up to set email alerts
|

Doubly fused fluorene embedded heterosapphyrins

Abstract: We report the synthesis of rare examples of nonaromatic doubly fused fluorene embedded heterosapphyrins by [3+2] condensation of 2,7-bis((1H-pyrrol-2-yl)(p-tolyl)methyl)-9H-fluorene (fluorene based tripyrrane) and [2,2'-bithiophene]-5,5'-diylbis(4-aryl)methanol] (bithiophene diol) in CH2Cl2 using BF3.OEt2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…A series of fluorene‐embedded macrocycles, including fluorenophyrin 5 and their oxa‐ 6 and thia‐derivates 7 , was reported by Ravikanth and coworkers [46–50] . The same group has also obtained the fluorenone‐embedded macrocycle 8 [51] …”
Section: Phenanthriporphyrin and Related Systemsmentioning
confidence: 93%
See 2 more Smart Citations
“…A series of fluorene‐embedded macrocycles, including fluorenophyrin 5 and their oxa‐ 6 and thia‐derivates 7 , was reported by Ravikanth and coworkers [46–50] . The same group has also obtained the fluorenone‐embedded macrocycle 8 [51] …”
Section: Phenanthriporphyrin and Related Systemsmentioning
confidence: 93%
“…A series of fluorene-embedded macrocycles, including fluorenophyrin 5 and their oxa-6 and thia-derivates 7, was reported by Ravikanth and coworkers. [46][47][48][49][50] The same group has also obtained the fluorenone-embedded macrocycle 8. [51] The Sessler group has introduced several systems incorporating dibenzo[g,p]chrysene moiety, e. g. 9, which can be perceived as a pair of twinned phenanthriporphyrins.…”
Section: Phenanthriporphyrin and Related Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…[11][12][13][14][15] In recent times, polyaromatic hydrocarbons/heterocycles (PAHs) were used in place of one or more pyrrole rings of porphyrinoids to generate a new type of polyaromatic embedded porphyrinoids with interesting electronic and coordination properties. [16,17] A perusal of literature revealed that the polyaromatic hydrocarbons/heterocycles such as biphenyl, [18] naphthalene, [19] phenanthrene, [20] fluorene [21,22] bipyridine, [23] phenanthroline, [24] dibenzofuran, [25] dibenzothiophene, [26] and phenothiazine [27] are few such polyaromatic hydrocarbons/heterocycles which have been introduced in place of one or more pyrrole rings of porphyrinoid framework and generated a wide range of very novel PAH embedded porphyrinoids. We used few of these PAH units such as dibenzofuran, dibenzothiophene, benzofuran, benzothiophene, fluorene and phenothiazine and synthesized very novel PAH embedded porphyrinoids which showed unique and interesting electronic and coordination properties.…”
Section: Introductionmentioning
confidence: 99%
“…Replacement of one or two pyrroles of tetrapyrrolic porphyrins with polyaromatic hydrocarbons/heterocycles (PAHs) resulted in the formation of new types of PAH embedded porphyrins which have received significant attention in recent years because of their unusual and unique characteristics. In recent times, polyaromatic hydrocarbons such as biphenyl [1,2] 1, phenanthrene [3][4][5][6][7] 2 and polyaromatic heterocycles such as phenanthroline, [8] bipyridine [9,10] 3, dibenzothiophene [11] 4, dibenzofuran, [12] benzothiophene [13] /furan, fluorene [14][15][16][17] embedded porphyrins and expanded porphyrins have been synthesized (Scheme 1) and the studies showed that the electronic properties were significantly altered by incorporation of PAH in place of pyrrole ring(s) of porphyrinoids. Furthermore, PAH embedded porphyrinoids have been seen to possess the following unique features (1) stabilizes metals in unusual oxidation states; [18,19] (2) forms organometallic complexes readily by creating unique macrocyclic environment for coordination;…”
Section: Introductionmentioning
confidence: 99%